2012
DOI: 10.1504/ijsdes.2012.051479
|View full text |Cite
|
Sign up to set email alerts
|

Summer-time thermal comfort in vernacular earth dwellings in Yazd, Iran

Abstract: There is widespread assumption that vernacular earth dwellings in hot climates, particularly those in central Iran are climate-responsive and provide thermal comfort in hot periods even without the aid of electro-mechanical cooling systems. The paper describes two surveys undertaken to investigate the provision of comfortable indoor temperatures in vernacular central-courtyard earth dwellings in Yazd in hot seasons. Firstly, a thermal comfort survey established the comfort temperature for the residents of vern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…In other words, the buildings in this wing are closed or have few transparent surfaces in order not to expose the spaces directed to the south to sunlight too much [34]. Briefly, the spaces in the south of the courtyard and the openings facing the north (courtyard) are planned as summer wings, and the spaces in the north of the courtyard and facing the openings in the south (courtyard) are planned as winter wings which is illustrated in Table 3 [35][36][37][38][39][40]. Seasonal Part…”
Section: Summer Wintermentioning
confidence: 99%
“…In other words, the buildings in this wing are closed or have few transparent surfaces in order not to expose the spaces directed to the south to sunlight too much [34]. Briefly, the spaces in the south of the courtyard and the openings facing the north (courtyard) are planned as summer wings, and the spaces in the north of the courtyard and facing the openings in the south (courtyard) are planned as winter wings which is illustrated in Table 3 [35][36][37][38][39][40]. Seasonal Part…”
Section: Summer Wintermentioning
confidence: 99%
“…Keshtkaran (2011) [15] presented data to prove the harmony between climate and architecture of Yazd. Foruzanmehr surveyed different elements of Yazd's vernacular architecture, their performance and role in dwellers' lives through several studies [8,12,[16][17][18][19] and concluded that vernacular houses provide a more comfortable living environment compared to modern apartments in most cases. Khalili and Amindeldar (2014) [13] studied the logic and performance of traditional solutions in low-E vernacular buildings of hot-arid regions in Iran and concluded that these buildings provide a sustainable environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, Sistan Kolaks are one-sided because prevalent winds blow only in one direction (Figure 15). The economic success in mid-nineteenth century encouraged more elaborate wind-catchers in Yazd [16]; thus, different sizes and forms of Yazd wind-catchers also represent the socio-economic situation of the house owners ( Figure 32). Sistan, on the other hand, did not experience the same economic boom and even today is one of the most destitute regions of the country with a feeble agricultural based economy [65].…”
Section: Wind-catchersmentioning
confidence: 99%
“…Apart from a limited number of research projects -for example, the works carried out by Foruzanmehr (2010Foruzanmehr ( , 2012 and Foruzanmehr and Vellinga (2011) -there is a lack of published research on the practical issues vernacular houses are having with regard to the provision of thermal comfort. In particular, there is a lack of understanding on how Downloaded by [University of Exeter] at 14:15 05 August 2015…”
Section: Gap In Knowledgementioning
confidence: 99%
“…Good agreement was also found between the findings of this study and other previous field studies in terms of relationships between indoor-air and neutral temperatures. The neutral temperature (T n ) was dependent on the indoor temperature (T in ) based on the following equation (Foruzanmehr 2010(Foruzanmehr , 2012:…”
Section: Thermal Comfort and Temperature Variation Surveysmentioning
confidence: 99%